Sero-prevalance of Cryptococcal Antigenemia in HIV Positive Individual having CD4 Counts <100 Cells/mm3 - Khadka, Sundar; Kandel, Samikshya; Pandit, Roshan; Manjhi, Rosham; Dhital, Subhash; Baniya, Jagat Bahadur; Mishra, Shravan Kumar; Mahato, Raj Kumar (Nepal Journal of Biotechnology, 2021)
Cryptococcus neoformans is one of the foremost common opportunistic infectious agents in people living with Acquired Immuno Deficiency Syndrome (AIDS). It has been reported to cause about 1 million cases of cryptococcal meningitis per year among HIV/AIDS and 600,000 deaths annually. This study was done to find the prevalence of Cryptococcal antigenemia among HIV positive individuals having CD4counts <100 cells/mm3. A cross-sectional study was conducted in the HIV Reference unit, National public health laboratory from July to December 2015. The study comprised of 99 HIV positive individuals having CD4counts <100 cells/mm3. CD4 T cell count was performed by flow cytometry (BD Biosciences, San Jose, CA, USA) and Cryptococcal antigen test by Latex agglutination assay. The overall prevalence of cryptococcal antigenemia was found to be 18.2%. Of the total ninety-nine subjects enrolled in the study, 72 (72.8%) were males and 27 (27.2%) were females. The mean age of the patients was 38 years ranging from 13 to 69 years. Higher percentage of female (22.2%) showed Cryptococcal infection in our study as compared to male (16.7%). The study concludes higher prevalence of Cryptococcal antigenemia among HIV infected individuals and recommends Cryptococcal antigen screening to be made mandatory in HIV positive patients having CD4 T cells count below 100/μl.